Peran Semiotika Umberto Eco dalam Jurnalisme Investigasi: Studi Kasus Terbunuhnya Vina dan Eky di Cirebon - Pranawukir, Iswahyu; Darmawan, Zakaria Satrio; Syarah, Maya May; Kusuma, Ema; Setianti, Yanti (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This study examines the application of Umberto Eco’s semiotics in investigative journalism, focusing on the news coverage of the Vina and Eky murder case in Cirebon. The research analyzes the news article titled "Initial Evidence of Vina’s Case Did Not Use Scientific Investigation, Convict’s Legal Counsel: This is the Beginning of the Problem," published on June 22, 2024, by Kompas. The primary objective is to explore how Eco’s semiotic theory shapes the narrative of this murder case and how symbols, signs, and narratives influence the public’s perception of truth and professionalism in criminal investigations. The study employs a qualitative approach, using semiotic analysis on relevant news texts. Data were collected from articles and related reports on the Vina and Eky cases. The findings reveal that Eco’s semiotic theory is highly relevant for understanding how meaning is constructed and presented in news narratives. The Vina and Eky case illustrates how factual reporting can intertwine with subjective interpretations, impacting public opinion and the judicial process. The study uncovers a tension between journalistic freedom and the need to maintain factual accuracy, along with the role of law enforcement professionalism in addressing biased or manipulative narratives. It concludes that Eco’s semiotics offers valuable insights for analyzing crime-related news, helping journalists and law enforcement navigate the complexities of biased information while upholding investigative integrity. This research underscores the importance of balancing journalistic freedom, truth, and professionalism in investigative reporting